The Inverted Okun's Law: Evidence from France - Verne, Jean-François (Review of Economic Analysis, 2025)
This study considers the nonlinear relationship between GDP growth and unemployment in France (1975–2024) using a logistic smooth transition regression (LSTR) model. Findings reveal a threshold unemployment rate of 7.93%, above which the traditional Okun’s law holds (GDP growth reduces unemployment). Below this threshold, an inverted Okun’s law emerges, where economic growth coincides with rising unemployment. This is explained by technological advancements, skill mismatches, and delayed employment adjustments. The results indicate that macroeconomic policies based on linear assumptions are limited in their capacity to address unemployment challenges effectively. Recognizing these nonlinear dynamics is crucial for designing effective labor market policies that account for asymmetries in economic fluctuations.